Hidradenitis suppurativa in a patient with hyperandrogenism, insulin-resistance and acanthosis nigricans (HAIR-AN syndrome) - Yaser Taha Melibary (PAGEPress Publications, 2018)
The author reports a rare presentation of hidradenitis supprutiva (HS) in combination with hyperandrogenism, insulin-resistance and acanthosis nigricans (HAIR-AN syndrome) in a female patient. Recently many clues have improved the understanding of HS as a systemic disease rather as a disease only with dermatological manifestation. This report might give another hint emphasizing the endocrinological and hormonal role in HS.